2023
DOI: 10.3389/fimmu.2023.1049393
|View full text |Cite
|
Sign up to set email alerts
|

Risk of hospitalization and vaccine effectiveness among COVID-19 patients in the UAE during the Delta and Omicron outbreaks

Abstract: IntroductionA rapid increase in COVID-19 cases due to the spread of the Delta and Omicron variants in vaccinated populations has raised concerns about the hospitalization risk associated with, and the effectiveness of, COVID-19 vaccines.MethodThis case–control study aims to determine the hospitalization risk associated with the inactivated BBIBP-CorV (Sinopharm) and mRNA BNT162b2 (Pfizer–BionTech) vaccines, and their effectiveness reducing the rate of hospital admission between 28 May 2021 and 13 January 2022,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…The association of COVID-19 infection, hospitalization and death with vaccination status was performed by stepwise multivariate logistic ordinal regression. From this analysis, different models were performed to calculate odds ratios (OR) and 95% confidence intervals (CI) for each outcome of interest and from these OR (25,(66)(67)(68)(69)(70)(71).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of COVID-19 infection, hospitalization and death with vaccination status was performed by stepwise multivariate logistic ordinal regression. From this analysis, different models were performed to calculate odds ratios (OR) and 95% confidence intervals (CI) for each outcome of interest and from these OR (25,(66)(67)(68)(69)(70)(71).…”
Section: Discussionmentioning
confidence: 99%
“…Three main outcomes were analyzed, (a) Infection (yes, no) (b) Hospitalization (yes, no), and (c) Death secondary to COVID-19 complications (yes, no). VE was calculated with the following formula: VE = (1 − OR) × 100% this method is widely used to calculate vaccine effectiveness (25,(66)(67)(68)(69)(70)(71).…”
Section: Study Variables 211 Vaccine Effectivenessmentioning
confidence: 99%
“…The possibility of being admitted to a hospital from an emergency department. Omicron (Hazard Ratio 0.33, 95 percent CI: 0.30 to 0.33) was about one-third of Delta (Hazard Ratio 0.33, 95 percent CI: 0.30 =-098721 [8] Study from African population showed that in the early stages of the fourth wave in South Africa, a different pattern of features and outcomes was found in patients hospitalized with COVID-19 compared to earlier waves, with younger patients having fewer comorbidities, fewer hospitalizations, and lower respiratory rates. [2] COVID-19 immunization, including a booster dose, was linked to a decreased risk of intensive care unit admission in people hospitalized with SARS-CoV-2 infection during Omicron predominance.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of 2020, after numerous experimental studies [ 1 , 2 , 3 , 4 ], different types of vaccines against the coronavirus disease of 2019 (COVID-19) became available in the wider population, as one of the most significant and effective measures to prevent COVID-19. Then, real-life observational studies showed the protective effect of vaccines in different parts of the world and in different populations [ 5 , 6 , 7 , 8 , 9 ]. The widespread uptake of COVID-19 vaccines has become the most powerful weapon in controlling the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%